INDIEFAB™ AWARD WINNERS. (Foreword Reviews)
The article announces the 2013 Indiefab Award given to independent book publishers, including the book "The Mountain Place of Knowledge," by Marshall Chamberlain in the Adult Fiction Action Adventure category, "Dead of Knight," by Nicole J. Persun in the Adult Fiction Fantasy category, and "The Expedition Book 2," edited by Jason Lewis and Tammie Stevens in the Adult Nonfiction Adventure & Recreation category.